Modern phenotyping platforms and their application in plant biology and agriculture - Shashko, Antonina Yu.; Bandarenka, Uladzislau Yu.; Charnysh, Maryia A.; Przhevalskaya, Darya A.; Usnich, Saveli L.; Pshybytko, Natalia L.; Smolich, Igor I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2020)
Phenotyping platforms is hardware and software systems that provide collection and processing of information about plant or other organism phenotypes. In the presented study, an analytical review of the phenotyping platforms of the world’s major manufacturers, their components, characteristics and applications in biology, agriculture and biotechnology was carried out. A comparison of the phenomics attitudes by key parameters was made, trends in the development of their sensory and program-analytical components were revealed. The assessment of the world market of phenotyping systems current state was made. The most important examples of phenomics facilities use for phenotyping in the field and laboratory conditions, fundamental and practical research in various fields of plant biology are given.